Recurrent and locally malignant osteoma in the skull - Łożyńska-Podhrebelna, Diana; Ziółkowska, Ewa (Contemporary Oncology/Współczesna Onkologia, 2003)
This paper presents a rare case of osteoma. The tumours developed in a number of skull bones of a 36-year-old woman and involved the sphenoid and temporal bones, the yoke-bone and the maxilla at the right-hand side as well as both parietal bones. The tumours grew slowly over a period of 14 years and then the rate of growth increased suddenly. This resulted in many clinical symptoms caused by the compression of intracranical softer structures (such as the right-hand temporal lobe and the optic nerve). Therefore surgical treatment was carried out three times between February and May 2001. But in spite of that treatment there was still a great risk of recurrence and a further growth of these tumours localized close to vital parts of the brain. Thus radical surgical excision was not possible. For this reason a few months later, in November 2001, an external beam radiation therapy was performed. The dose used in this case was 50 Gy at conventional fractionation (25 daily fractions, 6 fractions in a week). 6 MeV photon beams were applied. It was a CT-based conformal radiotherapy and a multi-leaf collimator was used. There were four radiation therapy portals designed to encompass the bone masses at the skull base. The MRI examinations of the head carried out 11 and 15 months after the radiotherapy showed no progression of the disease and no lesion of the brain after the irradiation. After this treatment some of the symptoms (such as headaches and dizziness) disappeared and the patient’s state of health became stabilized. The latest clinical examination of the patient took place in July 2003 (20 months after the radiotherapy).